Approach to the Chemotaxonomic Characterization of Traditional Cultivation Grape Varieties through Their Varietal Aroma Profile - Ángela Díaz-Fernández; Emilia Díaz-Losada; Sandra Cortés-Diéguez (Foods, 2022)
In this study, the aroma profile of 12 minority grape varieties of Vitis vinifera L., included in the ‘Caiño group’, was defined along three vintages by solid phase microextraction followed by the gas chromatography–mass spectrometry method (SPME-GC-MS). Principal objectives were to assess the aromatic profile as a useful fingerprint to differentiate them, recover traditionally cultivated grape varieties for the differentiation of an important wine-growing area and discover their chemotaxonomic potential. In each variety, free and bound volatile profile was carried out by grouping varietal compounds into thirteen families. In total, 339 volatile compounds were identified, 230 as free forms and 205 as aromatic precursors. Remarkable quantitative differences were observed between aromatic profiles for terpenes in the free fraction and for C6 compounds, alcohols, sesquiterpenes and phenols in the glycosidic fraction. Principal component analysis based on their aromatic profile highlights a good differentiation between varieties and suggests a certain degree of aromatic chemotaxonomic proximity between previously known parental varieties, ‘Caiño Blanco’ with respect to ‘Caiño Bravo’ and ‘Albariño’. This study shows the preliminary results of a large research project involving a larger number of grape varieties and thus a broader spectrum of genetic relationships between them.